2002
DOI: 10.1034/j.1600-0447.2002.02139.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative symptoms in first episode non‐affective psychosis

Abstract: Negative symptoms that are independent of the influence of positive symptoms, depression and extra pyramidal symptoms (EPS) are present in a substantial proportion of first episode psychosis patients and delay in seeking treatment is associated mainly with avolition and anhedonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 39 publications
(43 reference statements)
7
78
1
2
Order By: Relevance
“…less than 9 months) might therefore have a greater impact on negative symptoms than the same reduction in someone with a DUP greater than nine months. These findings are in accordance with the findings of the TIPS study and the study of Malla et al (2002Malla et al ( , 2004, both of which suggested that reduction of DUP may be as important for improving the severity of negative symptoms as it is for positive symptoms (Melle et al, 2008). Our finding of a non-linear association between DUP and negative symptoms is similar to that reported by Drake et al for total PANSS scores (Drake et al, 2000) albeit in a small sample with a short follow-up.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…less than 9 months) might therefore have a greater impact on negative symptoms than the same reduction in someone with a DUP greater than nine months. These findings are in accordance with the findings of the TIPS study and the study of Malla et al (2002Malla et al ( , 2004, both of which suggested that reduction of DUP may be as important for improving the severity of negative symptoms as it is for positive symptoms (Melle et al, 2008). Our finding of a non-linear association between DUP and negative symptoms is similar to that reported by Drake et al for total PANSS scores (Drake et al, 2000) albeit in a small sample with a short follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…Negative symptoms are associated with poor functional outcome (Malla et al, 2004), cognitive deficits (Heydebrand et al, 2004), social dysfunction and poor quality of life (Addington and Addington, 1993;Schmitz et al, 2007;Petersen et al, 2008). Negative symptoms are common: the prevalence in short-term follow-up studies (up to 2.5 years) is about 45% (Pogue-Geile and Harrow, 1985;Malla et al, 2002Malla et al, , 2004, and in longer term studies (7.5-10 years) 20-30% (Herbener and Harrow, 2001). Schizophrenia Research 142 (2012) [12][13][14][15][16][17][18][19] There is no established treatment for primary negative symptoms (Kirkpatrick et al, 2006;Buckley and Stahl, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moving beyond the definition itself, studies investigating the factor structure of the construct [87][88][89][90] have revealed that negative symptoms usually cohere into two distinct, yet related, subdomains: diminished expression, consisting of affective flattening and poverty of speech; and amotivation, consisting of avolition, apathy, asociality, and hedonic deficits. In addition, recent research has been focusing in further refining the negative symptom construct, with the majority of studies exploring the anhedonia and amotivation symptom domain.…”
Section: Negative Symptoms: Evolution Of the Conceptmentioning
confidence: 99%
“…Accordingly, in the early stages of the disease, at the first-ep-isode [89] and during the proceeding years [98,99], the presence of this symptom cluster is one of the greatest barriers to the achievement of functional recovery. Moreover, before full blown psychosis occurs, during the so-called high-risk (HR) or prodromal state, negative symptoms and impaired social cognition have been associated with marked impairment in psychosocial function [100,101] which appears to be a core feature of the HR state and tends to be resistant to all types of treatment [102].…”
Section: Negative Symptoms and Psychosocial Functioningmentioning
confidence: 99%
“…The domain of attention on the SANS was also excluded from our analysis, as factor analyses from previous studies have shown that this domain, unlike others, loads on both negative and disorganization dimensions. 35,36 We assessed depressive symptoms using the Calgary Depression Scale (CDS). 37 …”
Section: Instruments and Assessmentmentioning
confidence: 99%